Answer:
k = 36
Explanation:
Given
(8x + 3k)(9x - 2) = 0
Equate each factor to zero and solve for x
9x - 2 = 0 ⇒ 9x = 2 ⇒ x =
![(2)/(9)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jktznck182tnm6caow67cec9mn3il2bara.png)
8x + 3k = 0 ⇒ 8x = - 3k ⇒ x =
![(-3k)/(8)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4t6vtxrd9wohg2myjaqmll447m4znwlg30.png)
The product of the solutions = - 3, thus
× -
= - 3, that is
-
= - 3 ( multiply both sides by 72 )
- 6k = - 216 ( divide both sides by - 6 )
k = 36